Phylogenetic analysis and antibiotic resistance of Shigella sonnei isolates. Issue 1 (28th April 2022) - Pakbin, Babak; Didban, Abdollah; Brück, Wolfram M; Alizadeh, Mehdi
Abstract: Shigellosis is one of the most important gastric infections caused by different species of Shigella, and has been regarded as a serious threat to public health. Lineage/sublineage profile of Shigella sonnei is strongly associated with the antibiotic resistance and population structure of this pathogen. In this study, we determined the phylogeny and antibiotic resistance profiles of S. sonnei strains, isolated from 1246 stool and 580 food samples, using multiplex PCR–HRMA genotyping and Kirby–Bauer disk diffusion methods, respectively. A total of 64 S. sonnei strains were isolated (13 food and 51 clinical isolates). Multiplex PCR–HMR assay was able to differentiate the lineages II and III, and sublineages IIIb and IIIc strains successfully considering the definite melting curves and temperatures. Lineage I and sublineage IIIa strain were not isolated in this study. We also demonstrated that most of the S. sonnei strains isolated from both food and clinical samples clustered within the lineage III and sublineage IIIc. Resistance against trimethoprim-sulfamethoxazole, tetracycline, chloramphenicol, and streptomycin antibiotics were the most prevalent phenotypes among the S. sonnei lineage III and sublineage IIIc strains. Abstract : We determined the phylogeny and antibiotic resistance profiles of S. sonnei strains and found most of the strains clustered within the lineage III and resistance against trimethoprim-sulfamethoxazole and tetracycline antibiotics.